Quality evaluation of case series describing four-factor prothrombin complex concentrate in oral factor Xa inhibitor-associated bleeding: a systematic review - Craig I Coleman; Olivia S Costa; William L Baker; Yuani Roman-Morillo; Kelly McNeil-Posey; Belinda Lovelace; C Michael White (BMJ Open)
Introduction As oral factor Xa (oFXa) inhibitor use has increased, so has publication of case series describing related bleeding managed with four-factor prothrombin complex concentrate (4F-PCC).Objective This review aimed to identify case series describing 4F-PCC management of oFXa inhibitor-related bleeding and appraise their methodological and reporting quality.Design We searched Medline and EMBASE (1 January 2011 to 31 May 2020) to identify series of ≥10 patients with oFXa inhibitor-related major bleeding given off-label 4F-PCC. Case series were evaluated using a validated tool adapted for this topic. The tool addressed patient selection, bleed/outcome ascertainment, causal/temporal association and reporting.Results We identified 14 case series. None had ≥100 patients (range=13–84), three were prospective, two detailed appropriate inclusion criteria and four noted consecutive inclusion. While 12 series provided clear/appropriate methods for diagnosis of intracranial haemorrhage (ICH); none did so for extracranial bleeds and it was not clear whether bleeding was adjudicated in any. Haemostatic effectiveness, thrombosis and mortality were together evaluated in 12 series, but only seven used validated methods to evaluate/diagnosis haemostasis in ICH, six in gastrointestinal bleeds, five in other bleeds and three in thrombosis. Independent adjudication of haemostasis (n=1) and thrombosis (n=2) was infrequent. Thirty-day follow-up for mortality and thrombosis was noted in five and seven series. Anticoagulation measurement/levels in at least some patients were conveyed in three series. Few series provided data on anticoagulant agent/dose (n=4), time from anticoagulant (n=4), time-to-reversal (n=7), baseline (n=7) or change (n=0) in neurologic function.Conclusions Although many case series describe off-label use of 4F-PCC for oFXa inhibitor-related bleeding, methodological flaws and/or poor reporting necessitates caution in interpretation.